Interaction orders of drug dealing spaces: local orders of sensemaking in a poor black American place - Duck, Waverly (Crime, law and social change, 2012)
Based on ethnographic data, this essay analyzes the social order properties of a poor urban street, in a small city in the northeast United States, on which drug dealing is the principle occupation. Rather than treating drug dealing as an agent of disorder, we focus on the order properties of drug dealing and the ordered character of the local code of conduct that develops around it. Like Sudhir Venkatesh (American Journal of Sociology 103:82-111, 1997) we examine the interface between drug dealing and the neighborhood. However, in this small urban space the drug dealers are not outsiders, rather, they are long term residents: established insiders who are well integrated into community life. As such their work practices and the requirements they place on behavior in public spaces impact the neighborhood in comprehensive ways. We detail the phenomenon Elijah Anderson called the "code of the street" (Anderson 1999) as a set of practices and social markers, a local Interaction Order (Goffman, American Sociological Review 48:1-17, 1983; Rawls, Sociological Theory 2:136-149, 1987), that furnishes basic day to day sensemaking tools for residents (Rawls 2009). We propose that this order has a constitutive character that furnishes stable expectations (Garfinkel 1963, 1967) for meaningful social action and identity in the neighborhood. In a context of industrial decline and urban poverty, drug dealing careers constitute a major socialization factor, that touches everyone here - especially children.